Efektivitas Metode Jigsaw Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fiqih - Muhammad Ilham Khalid Al-Faraby; Imas Siti Fuziah (Sekolah Tinggi Agama Islam Persatuan Umat Islam Majalengka, 2025)
This research is motivated by the low learning outcomes of students in Fiqh, caused by the frequent teacher-centered lecture-based learning, which tends to make students passive. Therefore, learning that encourages active student participation is needed to improve learning outcomes in accordance with the school's minimum completion criteria. Based on the above issues, the author formulated the following problem: